Long-term oncological outcome after thoracoscopic lobectomy for non-small cell lung cancer patients - Nakao, Masayuki; Ichinose, Junji; Matsuura, Yosuke; Nakagawa, Ken; Okumura, Sakae; Mun, Mingyon (Journal of Thoracic Disease, 2019)
Background: Thoracoscopic surgery (TS) has been used more commonly as a less invasive procedure for early-stage non-small cell lung cancer (NSCLC) than conventional thoracotomy (TH) in Japan. However, limited evidential data are available to compare the treatment efficacy of TS and TH. The purpose of this study was to retrospectively investigate the difference in the long-term outcome and invasiveness of TS and TH. Methods: Total 1,166 NSCLC patients who underwent surgery between 2005 and 2013 were enrolled. Of these, 844 patients underwent surgery via TH and 322 via TS. We compared several clinicopathological factors and the long-term outcome between the two groups. We performed propensity score matching analysis to minimize differences in the patient background and tumor states. Results: The TS group included more women, non-smokers or light smokers, and healthy patients. In the TS group, the disease states were significantly less aggressive. The TS group had a much better 5-year overall survival (OS) rate of 92.6% as compared to 76.7% in the TH group (P